Trust – a ‘New’ Institution to Improve Urban Governance - Edwards, Peter (AESOP, 2012)
More than a decade after the participatory turn in planning, it is time to assess whether participation has produced genuinely new practices or merely rebranded traditional approaches. Many participatory institutions, when evaluated against Arnstein’s (1969) ladder of citizen participation, remain at the lower rungs of informing and consultation, with few authorities redistributing power and resources to enable genuine citizen influence. Nevertheless, evidence suggests that efforts to move beyond these minimal levels of engagement can foster mutual trust between communities and planning authorities, strengthening the legitimacy and quality of planning decisions. This paper builds on Edwards (2009) by examining the interplay of power and trust in participatory planning exercises, using documentary analysis and narrative interviews with planning and community actors on the Gold Coast, Australia. By framing participation through the lens of trust, the paper provides an alternative perspective to power-focused analyses, arguing that trust is crucial for enhancing democratic legitimacy and improving urban governance.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: trust; participation; power; democratic legitimacy; planning decisions; collaborative planning; governance; Gold Coast; Australia